Microdosimetric investigation for multi-ion therapy by means of silicon on insulator (SOI) microdosimeter. (7th November 2022) - Sakata, Dousatsu; Lee, Sung Hyun; Tran, Linh T; Pan, Vladimir; Nakaji, Taku; Mizuno, Hideyuki; Kok, Angela; Povoli, Marco; Rosenfeld, Anatoly; Inaniwa, Taku
Abstract: Objective. Ion radiotherapy with protons or carbon ions is one of the most advanced clinical methods for cancer treatment. To further improve the local tumor control, ion radiotherapy using multiple ion species has been investigated. Due to complexity of dose distributions delivered by multi-ion therapy in a tumor, a validation strategy for the planned treatment efficacy must be established that can be potentially used in the quality assurance (QA) protocol for the multi-ion treatment plans. In previous work, we demonstrated that the microdosimetric approach using the silicon on insulator (SOI) microdosimeter is practical for validating cell surviving fraction (SF) of MIA PaCa-2 cells in the independent fields of helium, carbon, oxygen, and neon ion beams. Approach. This paper extends the previous study, and we demonstrate a microdosimetry based approach as a pilot study to build the QA protocol in the multi-ion therapy predicting the cell SF along the spread-out Bragg peak obtained by combined irradiations of He+O and C+Ne ions. Across the study, the SOI microdosimeter system MicroPlus was used for measurement of the lineal energy in individual ion fields followed by deriving the lineal energy of combined ion fields delivered by a pencil beam scanning system at HIMAC. Main results. The predicted cell SF based on derived lineal energy and dose in the combined fields was in good agreement with the planned cell SF by our in-house treatment planning system. Significance. The presented results indicated the potential benefit of the SOI microdosimeter system MicroPlus as the QA system in the multi-ion radiotherapy.